2014
DOI: 10.1016/j.ibusrev.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Economic slowdowns, hazard rates and foreign ownership

Abstract: This paper evaluates the link between foreign ownership and firm exit during crises, using a longitudinal micro dataset over an 18-year period. We address two main questions: first, if foreign affiliates have different failure rates than domestic firms during economic downturns, and second if the foreignness effect differs between two different economic downturns. The results partially confirm the liability of foreignness argument, suggesting that when the crisis was more pronounced at home than abroad, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 72 publications
4
24
0
Order By: Relevance
“…Turning now to the results for industry-specific variables, we find that the agglomeration variable has an inverted U-shaped relationship with firm survival, as indicated by the positive coefficient on the variable and the negative coefficient of its square, which concurs with the results of previous studies (Cala et al, 2015;Cainelli et al, 2014;Varum et al, 2014). The results show that specialization diminishes firm exit, which supports the findings of the descriptive analysis of firm survival in specialized districts, such as those seen in the Kemer and Belek tourism districts.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Turning now to the results for industry-specific variables, we find that the agglomeration variable has an inverted U-shaped relationship with firm survival, as indicated by the positive coefficient on the variable and the negative coefficient of its square, which concurs with the results of previous studies (Cala et al, 2015;Cainelli et al, 2014;Varum et al, 2014). The results show that specialization diminishes firm exit, which supports the findings of the descriptive analysis of firm survival in specialized districts, such as those seen in the Kemer and Belek tourism districts.…”
Section: Resultssupporting
confidence: 89%
“…A relatively high entry rate reflects tougher competition and may reduce the likelihood of survival for firms (Mata & Portugal, 2002;Taymaz & Özler, 2007;Resende et al, 2016), and the negative impact of this variable on firm survival is confirmed by a large number of studies (e.g. Varum & Rocha, 2012;Varum et al, 2014). Entry rate is computed as the number of new firms in a given sector and year divided by the total number of firms operating in that sector in the previous year.…”
Section: Industry-specific Variablesmentioning
confidence: 98%
See 2 more Smart Citations
“…It is noted that the contribution of the lack of qualified staff provides visibility given that as noted in Figure 2, is part of a necessary component for business development, without hesitation, this is due to the low levels of internationalization that would allow us an exchange not only of goods and services (Shearmur, Doloreux, & Laperrière, 2015;Meyer, Skaggs, Nair, & Cohen, 2015), but also of governmental support, which is another detailed contribution in Table 3 and in relation to 错误!未找到引用源。 which shows the correlation it has with little access to business incentives, which would promote technological resources necessary for business development; instead of seeing this as a disadvantage, it should be an open mouth for all those who are willing to be big business (Côrte-Real, Oliveira, & Ruivo, 2017), since Colombia is a country with great biodiversity and infinite possibilities to take advantage of this quality to make us known internationally. According to the research sample, it is considered that there is a lack of knowledge both to carry out a business activity and in the same way to obtain the resources to increase economic prospects (Varum, Rocha, & Valente da Silva, 2014), therefore, incentives are lacking through the entities endorsed to have a support that does not mean higher business costs; on the other hand, we are aware that do not have the technology to compete with large multinationals, and for this, SMEs require support. It is clear that the economic level in Colombia is taken advantage by strong firms economically and technologically, which complicates competing with this type of firms, since its have a wide recognition; financing, with qualified personnel and high innovative capacity.…”
Section: Data Collection and Analysis Of Resultsmentioning
confidence: 99%